[MEMORANDUM REGARDING SMOKING AND AIRLINE TRANSPORTATION] - CHILCOTE,SD JR (Tufts Archival Research Center, 2007)
Missing Attachments; Memorandum from Sam Chilcote to the executive committee regarding the aviation subcommittee hearing on smoking aboard aircraft. Reports various Senators and Representatives’ stance on the proposal following the hearing. Lists those who attended including flight attendants.